Employees’ performance in a Mexican government agency depends on satisfaction with feedback - López-Franco, Nora C.; Valdez-Cepeda, Ricardo D.; Torres-Romero, Adriana I.; Milburn-Díaz, Aarón (Acta Universitaria, 2019)
LKnowledge on the impact of feedback orientation measures and the effect of satisfaction with feedback on performance is scarce. Therefore, the aims of this study were: to identify the influences of feedback utility, accountability, self-efficacy and social awareness on satisfaction with feedback; and to define the effect of satisfaction with feedback on performance through regression analyses for the case of employees of a Mexican government agency. Then, two questionnaires were designed and applied. The first one considered the feedback orientation scale and 76 employees. The second questionnaire involved measures of in-role behavior and five managers. Almost 87% of the employees’ satisfaction with feedback variation is explained by the direct additive effects of utility, accountability, self-efficacy, and social awareness. The employees’ performance variation depends on satisfaction with feedback.